1 Prevalence of extra-cardiac findings detected by cardiac MRI in inherited vs acquired cardiovascular diseases. (18th April 2016) - Amadu, AM; Baritussio, A; Dastidar, A Ghosh; Rodrigues, JCL; Crivelli, P; Meloni, GB; Conti, M; Bucciarelli-Ducci, C
Abstract : Introduction: With its large field of view, Cardiovascular Magnetic Resonance (CMR) allows the detection of extra-cardiac pathologies (ECP). Both cardiologists and radiologists should be able to recognise ECP and identify those requiring further investigation. The aim of our study is to assess the difference in prevalence of ECP in patients with suspected inherited cardiac conditions vs acquired heart disease. Materials and methods: We reviewed 1.817 consecutive clinical CMR studies performed in the biggest CMR department in Southwest England to look for ECP. Demographic characteristics and scans indications were also recorded. For each scan the presence of ECP and its relevance (need for further investigation, i.e. suspected lung malignancy) was assessed. The internal record system (Picture Achievement and Communication System, PACS) was used to check whether the ECP were previously known, or whether it represents a new finding. Results: We analysed 1, 817 scans, referred for the assessment of inherited cardiac condition (Group A, n = 906) and acquired heart disease (Group B, n = 911). There was no significant difference in prevalence of ECP between the two groups (p = 0.63). ECP were found in 26% of patient in Group A, 4% of which requiring further assessment; 69% previously unknown (Figure 1 ). ECP were reported in 27% of patients in Group B, 5% requiring further assessment; 68% were previously unknown. Conclusion: One in four patient has an extra-cardiac finding and the prevalence of ECP did not differ in patients presenting with inherited conditions vs acquired heart disease.